Trends and projections of the disease burden of vitamin A deficiency in China from 1990 to 2021 - Chen, Feng; Gu, Zixue; Shi, Zheng; Li, Shiyun; Peng, Rong (Frontiers in Nutrition, 2025)
ObjectiveThe current systematic research on the disease burden of Vitamin A deficiency in China is limited. To analyze the trends in the disease burden of Vitamin A Deficiency (VAD) in China from 1990 to 2021 and predict future trends from 2022 to 2050, providing a scientific basis for the prevention of VAD in China.MethodsBased on the Global Burden of Disease (GBD) data, we extracted incidence, prevalence, and disability-adjusted life years (DALYs) for VAD in China from 1990 to 2021. The Joinpoint regression model was used to analyze temporal trends, calculating the estimated annual percentage change (EAPC) and its 95% confidence interval (CI). The Bayesian Age-Period-Cohort (BAPC) model was employed to integrate age, period, and cohort effects for predicting China’s VAD disease burden from 2022 to 2050.ResultsFrom 1990 to 2021, the Age-Standardized Incidence Rate (ASIR), Age-Standardized Prevalence Rate (ASPR), and Age-Standardized Disability-Adjusted Life Year Rate (ASR-DALYs) of VAD in China showed a significant downward trend, with Estimated Annual Percentage Change (EAPC) values of −5.31 (95% CI: −5.65 to −4.96), −5.31 (95% CI: −5.66 to −4.96), and −3.86 (95% CI, −4.84 to −2.86), respectively. The disease burden was higher in females than in males and higher in children than in adults. According to the BAPC model, the ASR-DALYs of VAD in China are expected to stabilize from 2022 to 2050, with a gradual decline from 3. 17/100,000 in 2022 to 2.70/100,000 in 2050. The ASIR and ASPR are projected to continue declining, with ASIR decreasing from 1,838. 15/100,000 in 2022 to 269.57/100,000 in 2050 and ASPR decreasing from 1,835.08/100,000 in 2022 to 267.89/100,000 in 2050.ConclusionWhile China’s VAD burden has shown sustained reduction, continued attention is needed for children and women to address the “hidden hunger” of micronutrient deficiencies. Future efforts should strengthen nutritional interventions and health education to further mitigate the disease burden.